Assessment of metal exposure (uranium and copper) by the response of a set of integrated biomarkers in a stream shredder - Tagliaferro, Marina Beatriz (2018)
Environmental pollution with toxic trace metals is of great concern for the environment and for public health. Here we assess the response of the shredder caddisfly Calamoceras marsupus to sub-lethal exposures to copper and uranium. As endpoints we used growth, feeding and growth efficiency, and a set of enzyme biomarkers (oxidative stress: glutathione-S-transferase and catalase; respiration: lactate dehydrogenase; and the activities of acetylcholinesterase and Na+/K+-adenosine triphosphatase). We found that survival, growth, feeding and growth efficiency were not affected by any of the copper (0, 35 and 70 μg L−1) or uranium (0, 25 and 50 μg L−1) conditions. However, catalase activity increased with increased copper concentration, from 0.20 to 0.85 nmol min−1 mg−1 protein (mean ± SE; p < 0.0001). Na+/K+ ATPase activity decreased with increased U concentration (from 0.16 ± 0.01 to 0.11 ± 0.01; mean ± SE; p < 0.001). The activities of LDH, GST and AChE enzymes did not differ across treatments. We concluded that CAT and Na+/K+-ATPase were the most sensitive biomarkers for copper and uranium respectively, at concentrations below levels that would affect growth and feeding.